Enhancement of Grid-based Virtual Infrastructure for Efficient Data Dissemination in WSN - Parsediya, Rishi; Sharma, Sanjiv (IJRDO -Journal of Computer Science Engineering, 2015)
Wireless Sensor Network is a new scenario of network in that energy consumption is more crucial issue for this network. In WSN, there are several types of nodes that are classified into tiny nodes and special events nodes. A huge sensor network has several techniques to divide a network into small grids. The proposed scheme facilitate the energy saving and time efficiency for both cluster head and base station. The simulation results and theoretical analysis exhibit that the proposed circular grid based scheme performs better rather than the existing data dissemination scheme such as rectangular grid based scheme. This research work focuses on energy conservation and time efficient in WSN using data dissemination techniques.